Cheese galore - Snow, Alan. (Oxford : Oxford University Press, 2008)
There is trouble in Ratbridge - both above ground in the town and underground, where the boxtrolls and cabbageheads live. And the awful Snatcher has plans to make the trouble oh so very much worse... Can Arthur and his friends summon up all their cunning and save the day? With nearly two hundred incredible black and white drawings, this is the third part of Alan Snow's astonishing illustrated journey into the unbelievably weird world of Ratbridge.
7.4
5-8.
5-8
Keywords: Magic -- Juvenile fiction; Trolls -- Juvenile fiction; Fantasy; Magic -- Fiction; Trolls -- Fiction; Magic -- Fiction; Trolls -- Fiction; Ratbridge (Imaginary place) -- Fiction; Fantastic fiction